KARAKTERISTIK NILAI GIZI DAN ORGANOLEPTIK COOKIES DARI BERBAGAI FORMULASI TEPUNG KOMPOSIT : STUDI PUSTAKA - Hastuti, Ari; Wahyuni, Sri; Faradilla, RH Fitri (Jurnal Sains dan Teknologi Pangan, 2022)
ABSTRACTThis review aimed to look at the nutritional value and organoleptic characteristics of cookies from various types of local food composite flour formulations. Composite flour is flour derived from tubers, nuts, or cereals with or without wheat or flour and is used as a raw material for food preparations. The process of various composite flour formulations is carried out to improve the characteristics of the resulting cookies. The results of the review show that the nutritional value of each product formulation is different, and food products produced from various composite flour formulations can meet the national standard (SNI). The results of the review show that the highest nutritional value for water content was found in the formulation of canna flour: soybean flour of 3.60%, the highest ash content was found in the formulation of wheat flour: black potato flour at 4.84%, the highest fat content was found in the formulation of taro tuber flour: green bean flour, the highest protein content was found in the formulation of canna flour: soybean flour of 18.91%, and the highest carbohydrate content was found in the formulation of mocaf flour: kepok banana flour of 70.36%. The highest organoleptic value for color (4.60) was found in the taro tuber flour-mung bean flour formulation, the highest aroma value (3.90) was found in wheat flour-black potato flour formulation, the highest texture value (3.95) was found in canna flour- soybean flour formulation, and the highest taste value (3.90) was found in taro tuber flour-green bean flour formulation. Keywords: nutritional value, cookies, composite flourABSTRAKReview ini bertujuan untuk melihat karakteristik nilai gizi dan organoleptik cookies formulasi berbagai jenis tepung komposit pangan lokal. Tepung komposit adalah tepung yang berasal dari umbi-umbian, kacang-kacangan, atau sereal dengan atau tanpa tepung terigu atau gandum dan digunakan sebagai bahan baku olahan pangan.  Proses formulasi berbagai tepung kompsit dilakukan untuk memperbaiki karakteristik cookiesyang dihasilkan. Hasil review menunjukkan bahwa nilai gizi setiap formulasi produk memiliki perbedaan, dan produk pangan yang dihasilkan dari formulasi berbagai tepung komposit dapat memenuhi Standar Nasional Indonesia (SNI). Hasil review menunjukkan bahwa nilai gizi  tertinggi untuk kadar air adalah formulasi tepung ganyong: tepung kacang kedelai sebesar 3.60%, kadar abu tertinngi yaitu formulasi tepung terigu: tepung kentang hitam sebesar 4.84%, kadar lemak tertinggi yaitu formulasi tepung umbi talas: tepung kacang hijau, kadar protein tertinggi yaitu formulasi tepung ganyong: tepung kacang kedelai sebesar 18.91%, dan kadar karbohidrat tertinggi yaitu formulasi tepung mocaf: tepung pisang kapok sebesar 70.36%. Nilai organoleptik tertinggi untuk warna adalah tepung umbi talas: tepung kacang hijau sebesar 4.60, nilai aroma tertinggi yaitu ormulasi tepung terigu: tepung kentang hitam sebesar 3.90, nilai tekstur tertinggi yaitu tepung ganyong: tepung kacang kedelai sebesar 3.95, dan nilai  rasa tertinggi tepung umbi talas: tepung kacang hijau sebesar 3.90.   Kata kunci:nilai gizi, cookies, tepung komposit